2008
DOI: 10.1111/j.1600-0897.2007.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Immune Regulation at the Interface During Early Steps of Murine Implantation: Involvement of Two New Cytokines of the IL‐12 Family (IL‐23 and IL‐27) and of TWEAK

Abstract: TWEAK is likely offering protection against the deleterious effects of TNF in implantation explaining embryo survival in a TNF-rich environment, and equal number of implants in both strains. However, there is a clear difference of protection in abortion-prone mating peaking in the abortion/resorption window but starting early, and therefore possible links with the prevention of abortion in CBA x DBA/2 matings by interfering with complement activation as recently described by Girardi et al. are discussed, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 51 publications
1
23
1
2
Order By: Relevance
“…It is known that IL-27 is elevated in the placenta and maternal serum during normal pregnancy. 26,27 We also investigated whether IL-27 receptors (gp130 and WSX-1) were detectable in umbilical cord blood NK cells, especially after stimulation with IL-27 and IL-12. Our results indicated that gp130 protein may be inducible, and that IL-27 takes a period of time (24e48 hours) for induction of its activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that IL-27 is elevated in the placenta and maternal serum during normal pregnancy. 26,27 We also investigated whether IL-27 receptors (gp130 and WSX-1) were detectable in umbilical cord blood NK cells, especially after stimulation with IL-27 and IL-12. Our results indicated that gp130 protein may be inducible, and that IL-27 takes a period of time (24e48 hours) for induction of its activation (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…One peculiar observation was the high expression of the salmon p19 paralogues and trout p19a in gonad, perhaps suggesting that an IL-23 isoform may have a role in the salmonid reproductive system. p19 is known to be expressed in the reproductive tract in mammals (Mas et al, 2008).…”
Section: Differential Expression and Modulation Of P19 Paralogues In mentioning
confidence: 99%
“…TWEAK экспрессирован в плаценте человека и мы-шей, и его содержание снижалось в мышиной моде-ли спонтанного аборта, а нейтрализация этого фак-тора in vivo приводила к усиленной резорбции пло-дов [75].…”
Section: другие факторыunclassified